Distribution of copper and zinc in the soil of an industrial zone in the city of Garešnica, Croatia - Medunić, Gordana (Array, 2009)
Summary: Soils from an industrial zone in Garešnica, Croatia have been analysed by EDXRF and XRD. In the area surrounding two adjacent factories named 'Bakrotisak' and 'Croatia Protekt', thirty soil sites (depth 5-15 cm) were sampled in December 2007, together with five soil sites from the forest (check samples) situated 0.5 km away. The locality was selected for its periodical, industrially induced environmental pollution which affects nearby streams and fish ponds, resulting in occasional fish kills in the region. Analysis included the determination of the soil mineralogy, total organic matter contents, cation exchange capacity, bulk multi-element composition and heavy metal levels in leachates (exchangeable fraction). Multi-element concentrations in the check samples constituted natural levels based on their perfect normal distributions. The Kruskal-Wallis test showed higher, statistically significant (P = 0.0005) concentrations of Cu in the soil surrounding 'Bakrotisak' compared to the check samples. Furthermore, leaching analysis confirmed the copper contamination of the 'Bakrotisak' soil by highly significant positive correlation (the Kendall's Tau correlation coefficient >0.99) between its extractable Cu and total Cu levels. Moreover, enrichment factors based on Al as a reference element were found to be >2 for approximately 50% samples of the 'Bakrotisak' soil, suggesting its moderate anthropogenic contamination